Factors associated with periodontal diseases in pregnancy: Findings of the 2015 Pelotas Birth Cohort Study - Luisa Jardim Corrêa de OLIVEIRA; Mariana Gonzalez CADEMARTORI; Camila Silveira SFREDDO; Mariângela Freitas da SILVEIRA; Fernando Celso BARROS; Marcos Britto CORREA; Flávio Fernando DEMARCO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Although periodontal disease is common during pregnancy, little is known about socioeconomic, behavioral, or biological determinants related to clinically assessed periodontal condition during this period. We assessed the prevalence of periodontal disease and associated factors in pregnant women. This population-based survey used data used from the 2015 Pelotas Birth Cohort Study, Brazil. Pregnant women expected to give birth between December 2014 and May 2016 were interviewed and clinically examined by trained dentist, with periodontal measures collected in all teeth, six sites per tooth. Outcomes were periodontitis (using the 2012 Centers for Disease Control and Prevention and the American Academy of Periodontology criteria) and gingivitis (by the 2018 European Federation of Periodontology/ American Academy of Periodontology classification). Multivariate hierarchical Poisson regression was used to assess the associations between socioeconomic, systemic, and clinical oral factors and periodontal disease. A total of 2,474 pregnant women participated in the study. Prevalence of periodontitis and gingivitis was 14.63% and 21.67%, respectively. Lower educational level and calculus were associated with higher prevalence periodontitis and gingivitis (P<0.05). Smoking was also associated with periodontitis (P=0.05), and lower frequency of toothbrushing (P=0.005) with gingivitis. Periodontal disease, especially gingivitis, was prevalent in pregnant women and their determinants were socioeconomic, environmental, and clinical oral health factors.